Parents' Strategies in Anticipating the Problem of Free Sex in Adolescents in East Senuro Village - Aprita, Dela; Helmy, Henny; Saputra, Ardi (Journal of English Language and Education, 2025)
This study aims to determine the strategies implemented by parents in anticipating the problem of free sex in adolescents in East Senuro Village. The background of this study is the phenomenon of adolescents who drop out of school due to involvement in free sex behavior, so they have to get married at an early age even though they are not mentally or emotionally ready. The method used in this study is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that parents in East Senuro Village have implemented various strategies in anticipating the problem of free sex in adolescents, including instilling religious values from an early age, providing appropriate and continuous education, and shaping children’s character through an emotional approach and role models in the family. This study is expected to contribute to the development of science, especially in the field of family education and protecting adolescents from deviant behavior.